The Determinants of Fuel Use in the Trucking Industry – Volume, Size and the Rebound Effect - Mulalic, Ismir (Proceedings from the Annual Transport Conference at Aalborg University, 2020)
We analyse the determinants of trucking firm fuel use. We develop a simple model to show that trucking firm fuel use depends, in addition to the fuel price and the traffic volume, also on the output of the trucking firm’s production process (the movement of cargo) measured in ton- kilometres, characteristics of the truck stock, and congestion. We also analyse the rebound effect for road freight transportation, i.e. the percentage of increased energy efficiency that does not result in the reduction of fuel used. For the purpose of analysing the rebound effect for road freight transportation, we decompose the standard definition of the rebound effect for motor vehicles, i.e. the elasticity of traffic volume with respect to fuel cost, into the elasticity by which changes in fuel costs affects freight activity and the elasticity by which changes in freight activity affect traffic volume. We estimate these elasticities using a simultaneous-equation model based on aggregate time-series data for Denmark for 1980-2007. Our best estimates of the short run and the long run rebound effects for road freight transportation are 19% and 28%, respectively. We also find that an increase in the fuel price surprisingly has a small but significant negative effect on the fuel efficiency (measured here as vehicle kilometres travelled (VKT) per litre of consumed fuel), i.e. a 1% increase in the fuel price decreases the fuel efficiency by 0.13% in the long run. However, less distance has to be driven for the same payload. An 1% increase in the fuel price decreases the VKT by 0.19% in the short run and 0.28% in the long run. Finally, a 1% increase in the fuel price results in a 0.19% reduction in the trucking firms’ overall fuel use.